Cold subduction zone in northern Calabria (Italy) revealed by lawsonite–clinopyroxene blueschists. (8th April 2020) - Tursi, Fabrizio; Bianco, Caterina; Brogi, Andrea; Caggianelli, Alfredo; Prosser, Giacomo; Ruggieri, Giovanni; Braschi, Eleonora
Abstract: Lawsonite blueschists are important markers of cold subduction zones, subjected to intense fluid circulation. This is because lawsonite preservation in exhumed blueschists and eclogites is typically linked to cold exhumation paths, accompanied by hydration. In the Catena Costiera (Calabria, southern Italy), lawsonite–clinopyroxene blueschists of the Diamante–Terranova Unit, affected by ductile shearing and retrogression, are exposed. Blueschists contain zoned clinopyroxene crystals, showing core–rim compositional variation from diopside to omphacite and hosting primary inclusions of lawsonite and titanite. Thermodynamic modelling of phase equilibria in the NCKFMASHTO system revealed peak metamorphic conditions of 2.0–2.1 GPa and 475–490°C for the Alpine subduction in Calabria. The subsequent post‐peak metamorphic evolution mainly proceeded along a decompression and cooling path up to 1.1 GPa and 380°C. The final exhumation stages are recorded in the sheared blueschists where a mylonitic to ultramylonitic foliation developed at 0.7 GPa and 290–315°C. Therefore, the P–T evolution of the Diamante–Terranova blueschists mostly occurred in the stability field of lawsonite, sustained by H2 O‐saturated conditions during the exhumation path. The results of this study indicate that the blueschists underwent peak metamorphic conditions higher than previously thought, reaching a maximum depth of 70 km under a very cold geothermal gradient ( 6.6°C/km), during the Eocene subduction of the Ligurian Tethys oceanic crust in Calabria.